Insider Trading Restrictions and Insiders’ Supply of Information: Evidence from Earnings Smoothing - Zhang, Ivy Xiying; Zhang, Yong (Contemporary Accounting Research, 2018)
ABSTRACT We exploit the setting of first‐time enforcement of insider trading laws to investigate the relationship between insider trading opportunities and insiders’ supply of information. Insider trading opportunities motivate insiders to reduce their supply of information by concealing firm performance, thereby increasing their information advantage over outsiders, resulting in higher insider trading profits. Using data from 40 countries over the 1988–2004 period, we find that reporting opacity, as captured by earnings smoothness, decreases significantly after the initial enforcement of insider trading laws in countries with strong legal institutions. The decrease in earnings smoothness is positively related to the strictness of insider trading laws. The decrease in earnings smoothness is also more pronounced for countries that have more persistent insider trading law enforcement and for countries that impose more severe penalties on insider trading cases. Further analyses show that the decrease in earnings smoothness following insider trading enforcement is concentrated among firms that are not closely held and among high‐growth firms. In addition to uncovering a channel through which insider trading restrictions affect the information environment, our evidence highlights the importance of country‐ and firm‐level governance structures in determining the consequences of insider trading restrictions.